2022
DOI: 10.3390/risks10120234
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Index Futures Trading Volume on Spot Market Volatility in a Frontier Market: Evidence from Ho Chi Minh Stock Exchange

Abstract: This analysis is the first to investigate the influence of index futures trading volume on spot market volatility for the Ho Chi Minh Stock Exchange (HOSE). The data utilized in this study are the daily VN30-Index futures contract trading volume starting at the inception date for the VN30-Index futures contract, 10 August 2017 and going through 10 August 2022. Using an autoregressive distributed lag (ARDL) bounds testing approach, the empirical findings reveal a positive relation between VN30-Index futures tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…To investigate the short-run and long-run effects of GPRs on the volatility of oil price, this study employs the Autoregressive Distributed Lag (ARDL) model which was developed by Pesaran et al (2001). The ARDL model has some advantages compared to other co-integration methods (Truong et al, 2022). The prominent advantage of this model over other alternative cointegration methods is that an error correction model (ECM) can be estimated from the ARDL model, hence the shortrun and the long-run effects of explanatory variables on the dependent variable can be simultaneously computed.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the short-run and long-run effects of GPRs on the volatility of oil price, this study employs the Autoregressive Distributed Lag (ARDL) model which was developed by Pesaran et al (2001). The ARDL model has some advantages compared to other co-integration methods (Truong et al, 2022). The prominent advantage of this model over other alternative cointegration methods is that an error correction model (ECM) can be estimated from the ARDL model, hence the shortrun and the long-run effects of explanatory variables on the dependent variable can be simultaneously computed.…”
Section: Methodsmentioning
confidence: 99%
“…Other research has shown that stock index futures trading can reduce the volatility of the spot market. Drimbetas (2007), Santoni(1987) and Robinson (1994) studied the Greek, United States and London stock markets respectively, and found a negative correlation between stock index futures trading activity and spot price volatility [4,5,6]. Robinson also concluded that the launch of the FTSE 100 stock index futures contract reduced spot market volatility by approximately 17%.…”
Section: Literature Reviewmentioning
confidence: 99%